2021
DOI: 10.1002/ece3.7511
|View full text |Cite
|
Sign up to set email alerts
|

Linking population‐level and microevolutionary processes to understand speciation dynamics at the macroevolutionary scale

Abstract: Although speciation dynamics have been described for several taxonomic groups in distinct geographic regions, most macroevolutionary studies still lack a detailed mechanistic view on how or why speciation rates change. To help partially fill this gap, we suggest that the interaction between the time taken by a species to geographically expand and the time populations take to evolve reproductive isolation should be considered when we are trying to understand macroevolutionary patterns. We introduce a simple con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 130 publications
(210 reference statements)
0
4
0
Order By: Relevance
“…For instance, the inability to reliably infer lineage fusion can complicate conclusions about phylogeographic congruence among co‐distributed species (Garrick et al., 2019 ). Likewise, fusion events may play important roles in adaptive radiations (Marques et al., 2019 ), and affect inferences about macroevolutionary processes such as speciation and extinction rates (Alencar & Quental, 2021 ; Dynesius & Jansson, 2014 ; Rosenblum et al., 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the inability to reliably infer lineage fusion can complicate conclusions about phylogeographic congruence among co‐distributed species (Garrick et al., 2019 ). Likewise, fusion events may play important roles in adaptive radiations (Marques et al., 2019 ), and affect inferences about macroevolutionary processes such as speciation and extinction rates (Alencar & Quental, 2021 ; Dynesius & Jansson, 2014 ; Rosenblum et al., 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Madagascar) in our study raises a concern that the absence of a geographical effect on the coexistence dynamics of lizards may simply be attributed to the potential relatively smaller geographic ranges of lizards compared with snakes in general. This implies that the perception of a geographical area of the same size would differ between lizards and snakes (see Alencar & Quental, 2021). If snakes possess larger geographic ranges, then being on an island, as defined here, might indeed facilitate coexistence.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the genetic distribution pattern of Taxus wallichiana suggested that the barrier of the Hengduan and Dabashan mountains may have caused allopatric speciation ( Gao et al., 2007 ). Therefore, early genetic divergence of H. lichiangensis was most likely attributed to the heterogeneous uplift in the STP, and the subsequent microevolutionary processes at the population level may be driven by effects of heterogeneous habitats such as topography, altitude and humidity ( Alencar and Quental, 2021 ).…”
Section: Discussionmentioning
confidence: 99%